PERAN OTORITAS JASA KEUANGAN CIREBON PADA PERLINDUNGAN KONSUMEN FINANCIAL TECHNOLOGY LENDING - Bakhri, Syaeful; Layaman, Layaman; Alfan, Muh Iqbal (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
The Financial Services Authority (itself is an institution that is independent and free from interference from other parties, which has the functions, duties and authority of regulation, supervision, inspection and investigation. Consumers themselves are one of the unimportant in running their business. From the government, they act really how to support customers with challenges faced by consumers, in terms of consumer financial services protection, the Financial Services Authority (OJK) and the government's extension of the peer to peer lending. The method used in this research is qualitative by using normative juridical. Data collection techniques were carried out using the triangulation method with observation, interviews and documentation. The efforts of the financial authorities related to consumer protection are already good with SATGAS Investment Alert, fintech emergency numbers, but it is still has not been maximized and needs to be increased again. The community itself still believes that applications with four or more stars and good reviews are official applications.